Contention about theory of evolution a century ago - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
Father Erich Wasmann, a German Jesuit, played the crucial role in the debates with monists on the interpretation of theory of evolution. He showed that monistic interpretation of this theory is not necessary, and he proposed theistic interpretation of evolution. In this paper the history of these debates, that took place in Germany in 1907 was presented together with the philosophical examination of the arguments used by opponents. The second part of this paper presents how those debates influenced philosophical and theological thought in Poland.